Enhancing Population Services Efficiency: Development a Village Population Administration Information System in Nagari VII Koto Talago - Engla Desita; Khairi Budayawan (Journal of Hypermedia & Technology-Enhanced Learning, 2024)
This study aims to develop a web-based population administration system for Nagari VII Koto Talago, focusing on improving the efficiency and effectiveness of population data management. Currently, population data in Nagari VII Koto Talago is managed using Microsoft Office and stored in physical ledger books, which leads to inefficiencies and increases the likelihood of errors. Public information services, especially in processing requests for official documents such as population referral letters, still rely on paper-based methods, resulting in lengthy processing times. The system development followed the Waterfall Method, with a particular emphasis on the implementation stage. The objective is to replace the outdated, manual system with a computerized system, optimizing the use of technology for data input, storage, and management. By employing CodeIgniter, PHP, and MySQL, the newly developed system offers improved accessibility, reduces processing time, and ensures more accurate data handling. The results of this study are expected to significantly enhance the quality of population administration services by streamlining processes and increasing service responsiveness to the community.